Distribusi dan Kelas Ukuran Panjang Kerang Darah (Anadara granosa) di Perairan Pesisir Kecamatan Genuk, Kota Semarang - Prasojo, Setyo Adi; Irwani, Irwani; Suryono, Chrisna Adhi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Anadara granosa are often called blood cockle because of a brownish red color of meat Anadara. This color is due to hemoglobin in the blood. This research was conducted in coastal waters district Genuk Semarang held in April to June 2009 using descriptive methods. The methods used to determination sampling location was purposive sampling methods. Samples were collected at intervals of once a month. The results that of distribution of A. granosa in Genuk District waters, Semarang. Found eight individuals in April, 30 individuals in May, and 1341 individuals in June. The highest abundance of A. granosa found at station I of 2314 ind / ha. Based on the classes of A. granosa in this area, the shells length variation have approximately uniform size but in this area more dominated by small and medium-sized A. granosa, whereas large shells were found relatively little, indicating that A. granosa in this area was undergoing to grow.